GAYA BAHASA DAN AMANAT KUMPULAN PUISI "KARYA SUKARNI" - Fitri Wulansari; Herlena Aliai; Oktriwati; Sinta Flora; Abdurrahman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Poetry is a form of literary work that possesses strong expressive power in conveying ideas, emotions, and life experiences through aesthetic and symbolic language. This study aims to analyze figurative language and moral messages in a collection of poems by Sukarni, including Guru Ku, Desaku, Sekolahku, Sahabat, Andai, Nyanyian Hati, Indonesiaku, and Kopi Hitam. This research employs a qualitative descriptive method with data collection techniques through library research and note-taking. Data analysis is conducted using content analysis. The results indicate that dominant figurative languages include metaphor, personification, simile, and repetition. The moral messages reflect educational, moral, social, and national values. This study is expected to enhance readers' appreciation of literary works, particularly poetry.